APPLICATION OF IN LAW PRINCIPLES IN THE DECISION MAKING OF VISIT VISA EXEMPTION POLICY IN INDONESIA - Hana Farah Dhiba (Polteknik Imigrasi, 2019)
The government's decision through Presidential Regulation No. 21 of 2016 concerning Visit Visa Free still leaves a myriad of question marks in the community. This policy is an implication of the government's steps to increase the number of international tourists to Indonesia. But in fact, what happens is not fully in accordance with what was announced. Some considerations related to this policy need to be explored further. The formulation of the problem examined in this paper is how to apply the Lex Superior Derogate Legi Inferiori principle and the Reciprocity Principle in making a Visa Visa Free decision making. The research method used is qualitative normative legal research and normative juridical approach. From the results of the study it can be seen that the decision on a visa-free visit policy deviates slightly from the principle of Lex Superior derogate legion inferiori and reciprocal principles. This is what needs to be explored further, so that how the future policies and decisions of the government remain in line with the principles of the applicable law in Indonesia